2004
DOI: 10.1086/422146
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Disease Progression among Patients Coinfected with HIV and Human T Lymphotropic Virus Types 1 and 2

Abstract: The goal of this study was to investigate clinical outcomes and survival probabilities among persons coinfected with human immunodeficiency virus (HIV) and human T lymphotropic viruses types 1 and 2 (HTLV-I/II). A nonconcurrent cohort study of 1033 HIV-infected individuals was also conducted. Sixty-two patients were coinfected with HTLV-I, and 141 patients were coinfected with HTLV-II. HTLV-I/II coinfection was highly associated with African-American race/ethnicity, age of >36 years, higher CD4(+) T cell count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
119
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 27 publications
6
119
1
3
Order By: Relevance
“…The number of deaths and AIDS-defining conditions did not show significant differences (Table 2). Although the numbers are small, this finding is consistent with the report by BEILKE et al 4 and with our observation for the complete population.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The number of deaths and AIDS-defining conditions did not show significant differences (Table 2). Although the numbers are small, this finding is consistent with the report by BEILKE et al 4 and with our observation for the complete population.…”
Section: Discussionsupporting
confidence: 94%
“…Most of them suggested that HIV/HTLV-I co-infection shortens the survival of these patients 6,12,16,18,22 . In contrast, a recent longitudinal retrospective study showed that the HTLV-I infection in persons with HIV was not associated with a shorter survival 4 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…However, other studies have shown that immunosupression per se should be related to expression of such conditions without a rise in HTLV viral load [5][6][7].…”
mentioning
confidence: 95%